The Effect of Employee Well-Being Programs on Employee Retention in the Flexible Work Era : A systematic review using bibliometric methods - fidyah yuli ernawati; Silvia Hendrayanti; Marsha Ayunita Irawati (International Journal of Business and Quality Research, 2025)
The development of the modern world of work is characterized by the increasing adoption of flexible work patterns and greater attention to employee welfare. This study aims to analyze trends and research developments related to the influence of work flexibility and employee welfare programs on employee retention in the flexible work era through a bibliometric approach. By analysing 200 articles published in reputable international journals during the period 2019–2024, the study found that work flexibility—such as self-paced scheduling and an independent workplace—as well as comprehensive well-being programs consistently contribute positively to employee satisfaction, loyalty, and retention. These findings are increasingly relevant amid changing preferences of millennials and Gen Z who highly value work-life balance and work autonomy. The analysis also shows that the integration of flexible work policies and comprehensive welfare programs can reduce stress levels, increase motivation, and create a work environment that supports employees' emotional attachment to the organization. The practical implications of this study emphasize the importance of developing an adaptive and employee-based human resource policy so that organizations can retain the best talent amid the dynamics of changing work patterns. The study also identifies future research agendas to deepen understanding of the relationship between work flexibility, well-being, and employee retention in an ever-evolving work context.